2021
DOI: 10.1186/s43046-021-00058-4
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal metastasis in solid tumours: our four cases and review of the literature

Abstract: Background Vaginal metastasis should be kept in mind when evaluating the staging tests of all cancers, especially endometrial cancer. Case presentation We present four patients with vaginal recurrence who recently applied to our clinic. Three cases were of endometrial cancer and one case of rectal cancer. All patients presented with vaginal bleeding. Conclusion Standard treatment for vaginal metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In 1906, Penham first described vaginal metastasis from RCC 6 . Geng et al reported in their study less than 90 cases of metastatic RCC in the vagina and, according to the medical literature, roughly 100 cases of metastatic RCC in the vagina have been reported thus far 4,7,8 . RCC presents with synchronous metastases in 18% of cases, and with metachronous metastases in 50% of cases, after nephrectomy 3,7,8 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In 1906, Penham first described vaginal metastasis from RCC 6 . Geng et al reported in their study less than 90 cases of metastatic RCC in the vagina and, according to the medical literature, roughly 100 cases of metastatic RCC in the vagina have been reported thus far 4,7,8 . RCC presents with synchronous metastases in 18% of cases, and with metachronous metastases in 50% of cases, after nephrectomy 3,7,8 .…”
Section: Discussionmentioning
confidence: 93%
“…The usual sites of metastases are lungs, bones, adrenal glands, liver, and lymph nodes, very rarely brain and vagina. In 70-80% of all kidney tumours, the clear cell renal cell variant is the most common one, which can metastasize in the vagina [2][3][4] . The median age of patients with metastatic ccRCC in the vagina is 57 years old, compared to that of patients with primary clear cell vaginal carcinoma, which is more common in younger women, with a median age of 18 years old 1,5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common clinical presentation was vaginal bleeding, which is similar to the signs of primary vaginal cancer. Other symptoms included vaginal discharge, staining, or a palpable mass [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the vagina is a common site of metastatic gynaecological cancer (eg, cervical cancer and endometrial cancer) either by direct extension or through haematogenous/lymphatic spread. Non-gynaecological tumours can also metastasise or directly extend to the vagina, while the origin of the tumours includes not only nearby organs, such as the bladder and rectum but also occasionally distant organs, such as the lung and breast 1 3. Therefore, primary vaginal malignancies should be classified only after excluding possible metastatic tumours of other origin 2…”
Section: Introductionmentioning
confidence: 99%